M-Payment Using Mobile Phone Application in University Utara Malaysia - Yahia, Raid AB K (2009)
Wireless technology has developed into one of today's hottest topics due to its ability to bring the power of communication and the Internet into the hands of users while overcoming temporal and spatial constraints. Students in University Utara Malaysia are facing some of problems in paying their bills and paying their tuition fees. Thus, every time they have to go to Jitra or Alor Star to pay for their internet or astro bills. Moreover, for their tuition fees, students have to withdraw money from their bank and then go to pay for their tuition fees. These consume a lot of money and time. In this study, M-payment system helps to make it much easier for student to make their payment and settle their bills and their tuition fees at their convenience by using their wireless devices.